2009
DOI: 10.2478/v10035-009-0104-z
|View full text |Cite
|
Sign up to set email alerts
|

Bile Infection and Bile Acids Concentration in Bile in Acute Biliary Pancreatitis

Abstract: Biliary stones are the most common etiology of acute pancretitis (AP). Pathomechanism of this etiology is based on common channel theory of Opie. Material and methods. 113 patients with ABP were included in the study -91 with mild and 22 with severe form of ABP. 17 patients with cholelithiasis and choledocholithiasis without ABP served as controls. All the patients were submitted to the same model of treatment. Endoscopic retrograde cholangiopancreatography (ERCP) with endoscopic sfi ncterotomy (ES) were perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
(75 reference statements)
0
1
0
Order By: Relevance
“…This only occurs in the course of cholestasis of the bile ducts. The studies on animal models have found that bile acids may damage pancreatic cells and initiate inflammatory processes in this organ [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…This only occurs in the course of cholestasis of the bile ducts. The studies on animal models have found that bile acids may damage pancreatic cells and initiate inflammatory processes in this organ [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%